Purification of recombinant human interleukin-3 expressed as inclusion bodies in Escherichi coli - Quy, Nguyen Thi; Khoa, Dao Trong; Huong, Duong Thu; Hong, Le Thi Thu; Hai, Truong Nam (Academia Journal of Biology, 2021)
Human interleukin-3 (IL-3) is a hematopoietic growth factor involved in the survival, proliferation and differentiation of multipotent hematopoietic cells. However, recombinant IL-3 is usually expressed as insoluble form (inclusion bodies) in Escherichia coli cells. This state of protein often shows no bioactivity. Herein, we report a simple method for solubilization, refolding and purification of recombinant human IL-3 expressed in E. coli cells. First, IL-3 was expressed in E. coli JM109 (DE3) after being induced with 0.05 mM IPTG at 25 oC. Under these conditions, IL-3 was produced as inclusion bodies with molecular weight of approximately 15 kDa on SDS-PAGE gel (14%). Next, IL-3 pellet was separated from the host soluble proteins using sonication followed centrifugation. Then, two strong denaturants such as urea or guanidine hydrochloride were used to test solubilization of the insoluble IL-3. After that, the resulting soluble IL-3 was renatured and subjected to gel filtration chromatography to collect purified IL-3 protein. Our results showed that fractionates contained a single band of IL-3 with recovery rate of about 30%. Several characteristics of recombinant IL-3 were then analyzed. The cytokine IL-3 showed its high purity with a sharp peak on RP-HPLC chromatagram. The Western blot showed a clear signal band on PVDF membrane to demonstrate its right antigenecity against human IL-3 antibody. Besides, amino acid sequence of this cytokine was confirmed by mass spectrophotometry method. The purified IL-3 cytokine is a potential material for further tests.